2020
DOI: 10.15295/bmij.v8i4.1606
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Individuals' Creativity Performance: Paternalist Leadership, Management Innovation and Psychological Ownership

Abstract: Paternalistic leadership, management innovation, psychological ownership and creativity performance are the most important approaches for organisations to gain a competitive advantage. This study aims to examine the impact of paternalistic leadership, management innovation, and psychological ownership on creativity performance. Besides, it aimed to provide recommendations based on results regarding the impact of paternalistic leadership and management innovation on psychological ownership and creativity perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…This will encourage employees to exhibit innovative behaviour, which will improve innovation performance at the organisational level. The results (Sözbilir, 2020) demonstrated that management innovation and psychological ownership had a favourable effect on creativity performance. The study (Adeshina Akinwumi et al, 2021) found that salary administration and conflict management were important predictors of organisational performance.…”
Section: ____________________________________________________________...mentioning
confidence: 88%
“…This will encourage employees to exhibit innovative behaviour, which will improve innovation performance at the organisational level. The results (Sözbilir, 2020) demonstrated that management innovation and psychological ownership had a favourable effect on creativity performance. The study (Adeshina Akinwumi et al, 2021) found that salary administration and conflict management were important predictors of organisational performance.…”
Section: ____________________________________________________________...mentioning
confidence: 88%
“…Effect size (f 2 ) explains the measure of the effect of the independent latent variable on the latent dependent variable (Sözbilir, 2020). Each Intrinsic religiosity (IR) with the value of f 2 =0.024, Extrinsic religiosity (ER) with the value of f 2 =0.023, and making a donation (MD) with the value of f 2 =0.022 has a small effect on Rational voting behavior (RV), separately.…”
Section: Pls Structural Modelmentioning
confidence: 99%